2003
DOI: 10.1007/s11894-003-0085-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bioactive agents on biliary motor function

Abstract: Our understanding of biliary motility under normal and pathophysiologic conditions is still incomplete, but there have been recent advances. Of particular interest are the mechanisms involved in gallbladder filling and emptying, with a focus on understanding the processes underlying impaired gallbladder emptying leading to gallbladder dyskinesia and the formation of gallstones or cholecystitis. The sphincter of Oddi (SO) is a complex neuromuscular structure. Recent studies have attempted to unravel the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Gallbladder mast cells would have the potential to contribute to pain generation by at least 2 mechanisms: sensitivity to distension as seen with mast cell degranulation in the gastrointestinal tract and through the generation of gallbladder spasms induced by mast cell products. For example, both histamine and cysteinyl leukotrienes increase the excitability of gallbladder smooth muscle and lead to contraction [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Gallbladder mast cells would have the potential to contribute to pain generation by at least 2 mechanisms: sensitivity to distension as seen with mast cell degranulation in the gastrointestinal tract and through the generation of gallbladder spasms induced by mast cell products. For example, both histamine and cysteinyl leukotrienes increase the excitability of gallbladder smooth muscle and lead to contraction [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…There are many neurotransmitters and/or neuromodulators that can influence SO motility 34 . Such agents may be part of the normal physiological regulation of SO function, and others are part of pathological conditions such as inflammation.…”
Section: Effect Of Inflammation On So Motilitymentioning
confidence: 99%
“…In the SO immunohistochemical studies have identified the presence of a number of neurotransmitters or neuromodulating agents, 34 with recent studies finding NO synthase, substance P and gastrin‐releasing peptide 14,35,36 . However presence of a neurotransmitter does not imply an effect on motility, as determined in the associated functional studies 36 .…”
mentioning
confidence: 98%
“…The SO displays spontaneous activity, which is primarily myogenic in nature, but is subject to regulation via extensive neural pathways and reflexes. SO motor activity is the complex integration of several signalling systems, which include neural inputs and the effects of bioactive agents (Toouli & Baker, 1991; Woods et al. , 2003a; Woods et al.…”
Section: Introductionmentioning
confidence: 99%